Crab Mentality: Penyakit Mental Interaksi Sosial - Indriyani; Nur Endah Safitri; Yulius Dani Nugraha (Literaksi: Jurnal Manajemen Pendidikan, 2023)
The purpose of this study is to find out the perspective of the knowledgeable YouTube channel entitled "Mental Disease: Crab Mentality, It's hard to see other people happy, it's nice to see other people suffer". In this study, the researcher used a descriptive qualitative method by taking notes because the source of the data was obtained by listening to oral narratives. that in terms of psychologist crab mentality this is an analogy of humans who are jealous of other people's success and try to block other people's happiness.